Effect of High Fat Diet on Body Weight, Visceral Fat Weight, and PPARG Expressions on Visceral Fat in Mice - Melyana, Cantika Putri; Rejeki, Purwo Sri; Mudjanarko, Sony Wibisono; Herawati, Lilik; Al-Arif, Mohammad Anam (Folia Medica Indonesiana, 2021)
Obesity becomes a global epidemic nowadays. The high-fat diet is used as an alternative therapy for obesity. The optimal composition of a high-fat diet to reduce body weight is still unknown. This study aimed to determine which components of a high-fat diet can decrease body weight, visceral fat, and PPARG expression of visceral fat. This study was conducted at the Faculty of Veterinary Medicine, Universitas Airlangga, for three months by using a randomized post-test only control group design. Fifty male mice, 2-3 months old, 18-30 grams were adapted for one week given standard diet AIN93-M, then mice were divided into five groups, namely K1 (control group, 12% fat, 20% protein, 62% carbs); K2 (30% fat, 60% proteins, 0% carbs); K3 (45% fat, 45% protein, 0% carbs); K4 (60% fat, 30% protein, 0% carbs); and K5 (75% fat, 15% protein, 0% carbs). Bodyweight was measured before and after treatment, then the visceral fat and PPARG expressions were evaluated. Statistical comparisons were performed using Statistical Package for the Social Sciences (SPSS) software. After treatment, there were forty-three mice. The body weight and visceral fat weight of the mice with a high-fat diet were decreased. The most significant changes in body weight were in K4 with -9,60 ± 3,806 grams reduction. The bodyweight of mice in K5, slightly increased than K2-K4. This could be caused by the hormesis phenomenon. PPARG expressions decreased in groups with a high-fat diet but increased in K5. The composition of a high-fat diet in group K4 was the most optimal to decrease the body weight, visceral fat, and PPARG expressions in mice